Inside Front Cover: Epigenetic regulation of neural N‐glycomics. Issue 22 (November 2016) - Kizuka, Yasuhiko; Nakano, Miyako; Miura, Yuki; Taniguchi, Naoyuki
Abstract : DOI:10.1002/pmic.201600053 Glycans are not directly encoded in genes while the structure of proteins are directly encoded in their corresponding genes. Glycans are produced by concerted actions of glycosyltransferases and glycosidases and their expression is regulated at various levels including epigenetics, mRNA (transcriptomics), protein (proteomics), and metabolytes (metabolomics). We showed epigenetic regulation of the structural changes of glycans in the nervous system. For more details, see the article by Yasuhiko Kizuka et al. on page 2854.